THE NAVIRON PATH OF CRAFTS TODAY AND ITS ROLE IN YOUTH MATURATION (American Journal of Pedagogical and Educational Research, 2023)
It is not for nothing that in our people they say no dice from craft. Our marriage is filled with sophistication and the favonity of the country increases due to the work of Master workers and carpenters, poor and poor people. Today, a business environment has been created in our country, and great attention is paid to crafts and entrepreneurship on a government scale. In particular, it can be said that the decision of our president on December 30, 2021 “on measures to further improve the system of support for craft activities”opened the door to huge opportunities for craftsmen.